JUSTICES’ FREEDOM OF CONSTITUTIONAL INTERPRETATION METHOD IN THE INDONESIAN CONSTITUTIONAL COURT - Mardian Wibowo (Fakultas Hukum Universitas Gadjah Mada, 2013)
This paper lays out the method of interpretation used by the Indonesian Constitutional Court in inter-preting the articles within 1945 Indonesian Constitution, primarily in judicial reviews and disputes on the authority of state organ. Among the existing and mostly applied interpretation methods injurisprudence, the Court does not consider it self bound by a single method. The resort to variousinterpretation methods, dependent on the nature of the case at hand, indicates that the Court is progressiveand tends to favour contextual approach. Nonetheless, since the Court is composed of nine differentindividuals, the interpretation approach will largely depend on each Justice’s legal thought. Tulisan ini mencoba menelusuri metode tafsir yang dipergunakan oleh Mahkamah Konstitusi dalam menafsirkan ketentuan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, terutama dalamperkara pengujian undang-undang dan sengketa kewenangan lembaga negara. Dari beberapa metode tafsiryang ada dan lazim dipergunakan dalam bidang ilmu hukum, ternyata Mahkamah Konstitusi tidak mengikatdirinya pada satu metode tafsir saja. Penggunaan beberapa metode tafsir oleh Mahkamah Konstitusi secarabergantian, tergantung perkara yang dihadapi, menunjukkan sifat progresif dan pemahaman kontekstual.Namun karena Mahkamah Konstitusi adalah kumpulan dari sembilan individu hakim konstitusi makametode tafsir yang dipergunakan sangat tergantung pada kecenderungan dari masing-masing hakim.